1998
DOI: 10.1111/j.1600-051x.1998.tb02375.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a potassium citrate, cetylpyridinium chloride, sodium fluoride mouthrinse on dentine hypersensitivity, plaque and gingivitis

Abstract: Home-use studies on dentine hypersensitivity have most commonly involved toothpastes and rarely have mouthrinses been employed. Potassium and/or fluoride toothpastes have been shown effective in the treatment of dentine hypersensitivity. The aim of this study was to evaluate the effectiveness of a total formulation, containing potassium citrate, sodium fluoride, cetylpyridinium chloride mouthrinse compared to the base rinse minus actives in the reduction of dentine hypersensitivity. The study was a randomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 25 publications
5
58
0
4
Order By: Relevance
“…A further three studies were excluded as these studies were either in-office [51, 73] or in vitro studies [76]. Five studies were also excluded as potassium-containing solutions/mouthwashes were used [46, 55, 58, 92, 95]. The Jalalian et al [66] study was also excluded since this was a study evaluating the efficacy of an KNO 3 application in reducing DH with full-crown preparations.…”
Section: Discussionmentioning
confidence: 99%
“…A further three studies were excluded as these studies were either in-office [51, 73] or in vitro studies [76]. Five studies were also excluded as potassium-containing solutions/mouthwashes were used [46, 55, 58, 92, 95]. The Jalalian et al [66] study was also excluded since this was a study evaluating the efficacy of an KNO 3 application in reducing DH with full-crown preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have evaluated active agents in mouthrinses and 2 of these have both potassium salts [44,60]. Neither of these well-designed studies demonstrated efficacy of the potassium nitrate or citrate agent, respectively.…”
Section: Potassium Saltsmentioning
confidence: 99%
“…Iontophoresis with 2% sodium fluoride [15] Desensitizing toothpastes/dentifrices [13,14] containing strontium salts, fluorides, formaldehyde, potassium salts like potassium nitrate [16], potassium chloride or potassium citrate [17] Nova Min Mouthwashes containing potassium nitrate and sodium fluoride [18,19], potassium citrate or sodium fluoride [20] or a mixture of fluorides [21]. …”
Section: In-office Agents At-home Agentsmentioning
confidence: 99%